An Early Viral Response Predicts the Virological Response to Ribavirin in Hepatitis E Virus Organ Transplant Patients. Issue 10 (October 2015) - Kamar, Nassim; Lhomme, Sebastien; Abravanel, Florence; Cointault, Olivier; Esposito, Laure; Cardeau-Desangles, Isabelle; Del Bello, Arnaud; Dörr, Gaëlle; Lavayssière, Laurence; Nogier, Marie Béatrice; Guitard, Joelle; Ribes, David; et al.
Abstract : Background: Ribavirin is efficient at treating chronic hepatitis E virus infection in solid-organ transplant patients. However, the early kinetics of viral replication under therapy and the impact of immunosuppressant regimens on viral replication are unknown: thus, determining the aim of our study. Methods: Thirty-five patients with a solid-organ transplant and chronic hepatitis E virus infection were given ribavirin for 3 months. The hepatitis E virus (HEV) RNA concentrations were determined before treatment, at days 7, 15, and 21 and at months 1, 2, and 3 during therapy and after ribavirin cessation. Results: A sustained virological response (SVR) occurred in 63%. Decreased viral concentration within the first week post-ribavirin therapy was an independent predictive factor for SVR, and a decreased HEV concentration of 0.5 log copies/mL or greater had an 88% positive predictive value. No correlation between ribavirin trough level on day 7 or at month 2 with a virological response or an SVR was observed. Before therapy, HEV RNA concentration was significantly greater in patients receiving mechanistic target of rapamycin inhibitor-based immunosuppression compared to patients given calcineurin inhibitors. The use of mycophenolic acid did not impact on the response to ribavirin. Conclusion: An early response to ribavirin can be used to define the optimal duration of therapy in the setting of HEV infection. Abstract : An early response to ribavirin can be used to define the optimal duration of therapy for hepatitis E virus (HEV) infection. A decreased HEV concentration of ≥0.5 log copies/mL in the first week after commencement of ribavirin therapy had an 88% positive predictive value for a sustained virologic response.